2012
DOI: 10.1097/jgp.0b013e3182487680
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Quality and Its Association With Delirium Among Veterans Enrolled in Hospice

Abstract: Objectives The objectives of this study were to describe sleep quality and evaluate the association of sleep quality with delirium onset amongst patients enrolled in hospice. Design The study utilized secondary data from a prospective, observational, longitudinal study. Setting Veterans enrolled in hospice were recruited from the Portland Veterans Affairs Medical Center, Portland, Oregon. Participants The cohort consisted of 105 patients, of whom 73% had at least one sleep measurement. Measurements Sle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 35 publications
(39 reference statements)
1
27
0
Order By: Relevance
“…11 Hugel et al reported that in their study of 73 patients with advanced cancer, 60% patients related their insomnia to uncontrolled physical symptoms (predominantly pain and urinary frequency). 10 Insomnia may be associated with daytime sleepiness, cognitive impairment, accidents/injuries, anxiety, 12 depression, 12 delirium, 13 fatigue and, unsurprisingly, impaired quality of life. 14 Insomnia is associated with suppression of the immune system, which may have implications in terms of development of infections, and also progression of cancers.…”
Section: Cme: Palliative Medicinementioning
confidence: 99%
“…11 Hugel et al reported that in their study of 73 patients with advanced cancer, 60% patients related their insomnia to uncontrolled physical symptoms (predominantly pain and urinary frequency). 10 Insomnia may be associated with daytime sleepiness, cognitive impairment, accidents/injuries, anxiety, 12 depression, 12 delirium, 13 fatigue and, unsurprisingly, impaired quality of life. 14 Insomnia is associated with suppression of the immune system, which may have implications in terms of development of infections, and also progression of cancers.…”
Section: Cme: Palliative Medicinementioning
confidence: 99%
“…Several studies have demonstrated that the sleep of individuals with delirium is often disrupted, particularly in the postoperative period, and in individuals at the end of life . Whether sleep disruption is an early symptom of evolving delirium or acts as a precipitant for delirium remains unknown …”
mentioning
confidence: 99%
“…7 Several studies have demonstrated that the sleep of individuals with delirium is often disrupted, particularly in the postoperative period, [9][10][11][12][13][14][15] and in individuals at the end of life. 16 Whether sleep disruption is an early symptom of evolving delirium or acts as a precipitant for delirium remains unknown. 6 A longitudinal study was conducted of individuals undergoing elective surgery to determine whether preoperative sleep disturbance predicts postoperative delirium, 17 but the sample population was relatively young (average age 66) and the sample size too small to consider potential covariates.…”
mentioning
confidence: 99%
“…Of the remaining eight sources, five were eliminated because all study participants: 1) had cancer diagnoses and 2) did not meet the definition of EOL. Three articles [12][13][14] were included for synthesis and analysis ( Fig. 1).…”
Section: Search Resultsmentioning
confidence: 99%
“…In a secondary data analysis of a prospective observational study of veterans in home hospice care, the association between disturbed vs. undisturbed sleep as measured by the Pittsburgh Sleep Quality Index [15] and QoL score, depression worsening, and onset of delirium during hospice was studied [14]. Quality of life score was rated by patients on a scale from 0 to 100, with higher numbers indicating better QoL.…”
Section: Study Resultsmentioning
confidence: 99%